Pengaruh Model Cooperative-Project Based Learning Untuk Mengembangkan Keterampilan Berpikir Kritis Mahasiswa - Retno Utaminingsih; Ayu Rahayu (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2019)
This study aims to determine the effect of cooperative-project based learning models to develop critical thinking skills of UST PGSD students in Science Concept Basic courses. The research method used a quasi-experiment with the Nonequivalent Control Group Design. The study was conducted on UST PGSD study program students. Data collection techniques using documentation techniques, test techniques and observation techniques of critical thinking skills. Data analysis consists of analyzing test results as well as analyzing the results of observations of critical thinking skills. From the results of different tests, the value of p = 0.000 was obtained so that there was a very significant difference in the achievement of critical thinking skills of students who took part in learning using conventional learning models and cooperative-project based learning models. Because the average grade of the class using the cooperative-project based learning model is higher than the average grade of the class using the conventional model, so there is an influence of the cooperative-project based learning model in developing critical thinking skills of USSD PGSD students in the Science Concept Basic course.